2022
DOI: 10.1007/s00198-022-06490-z
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of fallers who later sustain a hip fracture: a NOREPOS study

Abstract: Fall prevention programs have shown inconclusive results concerning hip fracture reduction. We found that fallers with poor health, low societal participation, and use of psychotropics/painkillers had a threefold to fivefold increased hip fracture risk compared to non-fallers without these risk factors. This may help target fall prevention towards high-risk individuals. Introduction To investigate whether self-reported information on health, societal participation, and drug use in older people, easily obtainab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 43 publications
1
1
0
Order By: Relevance
“…The findings from this study support prior research suggesting gender differences such that men post-hip fracture had more comorbidities, were more cognitively impaired, were less socially interactive, and spent less time in overall physical activity than women (Søgaard et al, 2022). In addition, model comparisons between genders supported evidence of differences between men and women.…”
Section: Discussionsupporting
confidence: 85%
“…The findings from this study support prior research suggesting gender differences such that men post-hip fracture had more comorbidities, were more cognitively impaired, were less socially interactive, and spent less time in overall physical activity than women (Søgaard et al, 2022). In addition, model comparisons between genders supported evidence of differences between men and women.…”
Section: Discussionsupporting
confidence: 85%
“…However, the existing literature does not clearly indicate whether weight loss is the key to improving balance in fall intervention programs. While one study found no significant difference in BMI between fallers and non-fallers [ 34 ], another study linked obesity to balance disturbances [ 35 ]. Our study population was clinically overweight, with a mean BMI of 27.6.…”
Section: Discussionmentioning
confidence: 99%